Some aspects of the productive biology of redtaila scad decapterus kurroides (Bleeker, 1855) - Fermaran, Michelle Joy L. (College of Fisheries, University of the Philippines, 2015)
Reproductive biology is an important part in formulating fisheries management tools. In this study, the reproductive biology of Decapterus kurroides caught by surrounding nets and landed at Miagao market from March to April was examined. In order to confirm that the samples collected were the target species, morphological characteristics of the samples were also taken and meristics of 2 samples was also recorded. The results have shown that the species measured were all D. kurroides. Length-weight and length-girth relationships of D. kurroides were also observed in this study, this is another necessary tool in the formulation of management technique. Negative allometric growth was observed in the LWR of D. kurroides which was shown by the value of b which is less than 3. Three lengths were used to analyze the growth; for standard length the value of b was 2.648, for the total length, 2.8633 and for the fork length 2.8364. For the LGR of the samples, positive linear relationship was observed which was shown by high value of R2 which is 0.8658. For the reproductive analysis of the samples, GSI, photos of the maturity stages and the length at 50% maturity of D. kurroides was examined. The lowest GSI which recorded was 0.016958 at length 125.93 which shows that the species starts to develop at this length. The histological analysis of the slides revealed that during the months of March and April, juvenile and spent samples are captured and length at first maturity of D. kurroides was recorded at 152.68.